Life expectancy and disease burden in the Nordic countries: results from the Global Burden of Diseases, Injuries, and Risk Factors Study 2017 - Ann Kristin Knudsen; Peter Allebeck; Mette C Tollånes; Jens Christoffer Skogen; Kim Moesgaard Iburg; John J. McGrath; Knud Juel; Emilie Elisabet Agardh; Johan Ärnlöv; Tone Bjørge; Juan J Carrero; Christopher R. Cederroth; et al. (Elsevier, 2019)
Summary: Background: The Nordic countries have commonalities in gender equality, economy, welfare, and health care, but differ in culture and lifestyle, which might create country-wise health differences. This study compared life expectancy, disease burden, and risk factors in the Nordic region. Methods: Life expectancy in years and age-standardised rates of overall, cause-specific, and risk factor-specific estimates of disability-adjusted life-years (DALYs) were analysed in the Global Burden of Diseases, Injuries, and Risk Factors Study (GBD) 2017. Data were extracted for Denmark, Finland, Iceland, Norway, and Sweden (ie, the Nordic countries), and Greenland, an autonomous area of Denmark. Estimates were compared with global, high-income region, and Nordic regional estimates, including Greenland. Findings: All Nordic countries exceeded the global life expectancy; in 2017, the highest life expectancy was in Iceland among females (85·9 years [95% uncertainty interval [UI] 85·5-86·4] vs 75·6 years [75·3-75·9] globally) and Sweden among males (80·8 years [80·2-81·4] vs 70·5 years [70·1-70·8] globally). Females (82·7 years [81·9-83·4]) and males (78·8 years [78·1-79·5]) in Denmark and males in Finland (78·6 years [77·8-79·2]) had lower life expectancy than in the other Nordic countries. The lowest life expectancy in the Nordic region was in Greenland (females 77·2 years [76·2-78·0], males 70·8 years [70·3-71·4]). Overall disease burden was lower in the Nordic countries than globally, with the lowest age-standardised DALY rates among Swedish males (18 555·7 DALYs [95% UI 15 968·6-21 426·8] per 100 000 population vs 35 834·3 DALYs [33 218·2-38 740·7] globally) and Icelandic females (16 074·1 DALYs [13 216·4-19 240·8] vs 29 934·6 DALYs [26 981·9-33 211·2] globally). Greenland had substantially higher DALY rates (26 666·6 DALYs [23 478·4-30 218·8] among females, 33 101·3 DALYs [30 182·3-36 218·6] among males) than the Nordic countries. Country variation was primarily due to differences in causes that largely contributed to DALYs through mortality, such as ischaemic heart disease. These causes dominated male disease burden, whereas non-fatal causes such as low back pain were important for female disease burden. Smoking and metabolic risk factors were high-ranking risk factors across all countries. DALYs attributable to alcohol use and smoking were particularly high among the Danes, as was alcohol use among Finnish males. Interpretation: Risk factor differences might drive differences in life expectancy and disease burden that merit attention also in high-income settings such as the Nordic countries. Special attention should be given to the high disease burden in Greenland. Funding: Bill & Melinda Gates Foundation. The work on this paper was supported by the Research Council of Norway through FRIPRO (project number 262030) and by the Norwegian Institute of Public Health.